Ultrasound assisted catalytic oxidative desulfurization of diesel oil using CdO nanoparticles. (3rd August 2018) - Yu, Xingming; Zhao, Meng; Han, Pingfang; Lu, Xiaoping
ABSTRACT: In this paper, sol-gel auto-combustion method is used to synthesize CdO nanoparticles. The synthesised sample is characterized for its size and structure using X-Ray diffraction (XRD) and scanning electron microscopy (SEM) techniques. And some molecular groups containing in the nanoparticle are detected by Fourier transformer Infra Red (FT-IR). Then, the sample is used to remove the organic sulfur from hydrogenation desulfurated diesel under ultrasonic condition. The influence parameters including catalyst dosage, oxidant dosage, oxidation temperature, oxidation time and extracting times are been researched. The obtained result indicates that under the optimal condition, the desulfurization degree can be reached 72.7%.